Trypanosome outer kinetochore proteins suggest conservation of chromosome segregation machinery across eukaryotes - D’Archivio, Simon; Wickstead, Bill (Rockefeller University Press, 2016)
Kinetochores are multiprotein complexes that couple eukaryotic chromosomes to the mitotic spindle to ensure proper segregation. The model for kinetochore assembly is conserved between humans and yeast, and homologues of several components are widely distributed in eukaryotes, but key components are absent in some lineages. The recent discovery in a lineage of protozoa called kinetoplastids of unconventional kinetochores with no apparent homology to model organisms suggests that more than one system for eukaryotic chromosome segregation may exist. In this study, we report a new family of proteins distantly related to outer kinetochore proteins Ndc80 and Nuf2. The family member in kinetoplastids, KKT-interacting protein 1 (KKIP1), associates with the kinetochore, and its depletion causes severe defects in karyokinesis, loss of individual chromosomes, and gross defects in spindle assembly or stability. Immunopurification of KKIP1 from stabilized kinetochores identifies six further components, which form part of a trypanosome outer kinetochore complex. These findings suggest that kinetochores in organisms such as kinetoplastids are built from a divergent, but not ancestrally distinct, set of components and that Ndc80/Nuf2-like proteins are universal in eukaryotic division.